The Role of Matrix Metalloproteinase2 (MMP2) in Serum and Peritoneal Fluid of Endometriotic Patients - Baharuddin, NurIedil; Abdullah, Nusratuddin; Tessy, Telly; Chalid, St Maisuri T; Chalid, St Maisuri T (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To determine the role of matrix metalloproteinase-2(MMP-2) in serum and peritoneal fluid of endometrioticpatients.Methods: Research’s design using cross-sectional method in Dr.Wahidin Sudirohusodo hospital and several other hospitals inMakassar within May 2015 until May 2016. Subjects were chosenusing consecutive sampling technique. The examination usingthe ELISA method. The data were analysed using Fisher exact,t-independent, Mann-Whitney, and Spearman association.Results: A total of 50 subjects were recruited in this study. Mostlythe value of MMP-2 serum and peritoneal fluid in endometriosisgroup was higher compare to study control. There was significantdifferent between the total of MMP-2 serum and peritoneal fluid.There was also a significant association between the value ofMMP-2 serum and peritoneal fluid with endometriosis.Conclusion: The value of MMP-2 serum and peritoneal fluid werehigher in endometriotic patients compared to those withoutendometriosis. The higher the value of MMP-2 serum andperitoneal fluid, the higher the stage of endometriosis.[Indones J Obstet Gynecol 2018; 6-2: 104-109]Keywords: endometriosis, matrix metalloproteinase-2, MMP-2